2015
DOI: 10.1371/journal.pone.0136572
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotective Effect of Echinocystic Acid, a Triterpone Component from Eclipta prostrata, in Ovariectomy-Induced Osteoporotic Rats

Abstract: Echinocystic acid (EA) is a natural triterpone enriched in various herbs and has been used for medicinal purposes in China. In the present study, we systematically examined the effects of EA on ovariectomy-induced osteoporosis in rats for the first time. Three-month-old female ovariectomy (OVX) Sprague–Dawley rats were used to evaluate the osteoprotective effect of EA. Results showed that administration of EA (5 or 15 mg/kg/day) for 12 weeks prevented lower levels of maximum stress and Young’s modulus of femur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Certain echinocystic acids exert anti-inflammatory, anti-apoptotic, antidepression, osteoprotective and anti-diabetic activities (Kumar et al, 2012;Deng et al, 2015;Yang et al, 2016). The molecular mechanisms of these actions are not clearly defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain echinocystic acids exert anti-inflammatory, anti-apoptotic, antidepression, osteoprotective and anti-diabetic activities (Kumar et al, 2012;Deng et al, 2015;Yang et al, 2016). The molecular mechanisms of these actions are not clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic activities of certain EAs derivatives are attributed to activation of JNK-and p38 kinase-mediated mitochondrial pathways and to regulation of protein expression of proapoptotic and antiapoptotic molecules (Tong et al, 2004a(Tong et al, , 2004bLee et al, 2005, Cho et al, 2016. Recently, the anti-depression, osteoprotective and anti-diabetic activities of EAs have also been proposed (Kumar et al, 2012;Deng et al, 2015;Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution order of the other tissues was as follows: spleen > lung > kidney > heart for ecliptasaponin IV, ecliptasaponin A, apigenin, luteolin and luteolin‐7‐ O ‐glucoside; kidney > spleen > lung > heart for 3′‐hydroxybiochanin A and wedelolactone. In total, all of the analytes could be detected in the selected organs, supporting the possibility that E. prostrata may have various activities (Chung et al, ; Deng et al, ; Lee et al, ; Liu et al, ; Tewtrakul et al, ).…”
Section: Resultsmentioning
confidence: 64%
“…Modern pharmacological studies have shown that E. prostrata possesses anti‐oxidant, anti‐inflammatory, anti‐proliferative and anti‐tumor effects (Lee et al, ; Liu et al, ; Pukumpuang et al, ; Tewtrakul, Subhadhirasakul, Tansakul, Cheenpracha, & Karalai, ). Chemical studies reveal that it contains various constituents, such as triterpenoid saponins, flavonoids, coumarins, steroids, thiophenes, alkaloids and essential oils (Chung, Rajakumar, Lee, Kim, & Thiruvengadam, ; Deng, Kang, Zhao, Liu, & Zhao, ; Han et al, ; Lee et al, ; Ogunbinu, Flamini, Cioni, Ogunwande, & Okeniyi, ; Pukumpuang et al, ; Tabata, Taniguchi, & Shibano, ; Xi et al, ; Xi, Li, Mi, Wu, & Chen, ; Zhang, Sun, Zhang, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Flowers throughout the year, a quantitative short-day plant abundant seeders. [12] Leaves are inverse, basic, harsh, dull green, praise to elliptical lanceolate, 2-10 cm long, 1-3 cm wide, zenith intense or gruff, base lessen, edge whole or somewhat serrate, pubescent, for the most part sessile, the lower leaves once in a while short-petioled, basally swollen hairs on the two surfaces, veins noticeable. Inflorescence: blossom goes to 1 cm in distance across, a group of sessile white blooms, in upper axils or terminal, lone or two heads together.…”
Section: Introductionmentioning
confidence: 99%